Physical Review C: Nuclear physics. Volume 83, Issue 1, January 2011 - American Physical Society (2011)
Physical Review C contains research articles reporting experimental and theoretical results in all aspects of nuclear physics, including the nucleon-nucleon interaction, few-body systems, nuclear structure, nuclear reactions, relativistic nuclear collisions, hadronic physics and QCD, electroweak interaction, symmetries, and nuclear astrophysics